Algebra and trigonometry - Stewart, James, 1941- 4 0 16; Redlin, L.,;Watson, Saleem; 5 (Singapore : Cengage Learning Asia, 2018)
This bestselling author team explains concepts simply and clearly, without glossing over difficult points. Problem solving and mathematical modeling are introduced early and reinforced throughout, providing students with a solid foundation in the principles of mathematical thinking. Comprehensive and evenly paced, the book provides complete coverage of the function concept, and integrates a significant amount of graphing calculator material to help students develop insight into mathematical ideas. --
Prerequisites -- Equations and graphs -- Functions -- Polynomial and rational functions -- Exponential and logarithmic functions -- Trigonometric functions : right triangle approach -- Trigonometric functions : unit circle approach -- Analytic trigonometry -- Polar coordinates and parametric equations -- Vectors in two and three dimensions -- Systems of equations and inequalities -- Matrices and determinants -- Conic sections -- Sequences and series -- Counting and probability
Includes index
Keywords: 2 -- 0; 6; Algebra;Trigonometry -- 20 -- Textbooks;Textbooks; 20; 2